2002
DOI: 10.1002/1439-7641(20020617)3:6<543::aid-cphc543>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Superlattice and Magnetism Directed by the Size and Shape of Nanocrystals

Abstract: With a baton the general directs soldiers and the conductor musicians, and in the nanoworld the rodlike shape also means control, as this form enhances magnetic and coercive properties of crystalline aggregates. Also reported here is a tunable synthetic method, in which the overall shape of the crystal is determined by a balance of kinetically and thermodynamically controlled growth mechanisms. The graphic shows one example of the degree of ordering available in the crystalline through this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 10 publications
7
84
0
5
Order By: Relevance
“…Park et al studied the structural change of Co nanocrystals, and proposed that the formation of hcp structure is a delicate balance between kinetic and ther- modynamic growth regimes. The growth temperature and time were the important parameters for the control of the structure and shape of the Co nanocrystals [39]. In this study we found that the concentration of oleylamine is critical for the formation of hcp Ni.…”
Section: Refsmentioning
confidence: 95%
“…Park et al studied the structural change of Co nanocrystals, and proposed that the formation of hcp structure is a delicate balance between kinetic and ther- modynamic growth regimes. The growth temperature and time were the important parameters for the control of the structure and shape of the Co nanocrystals [39]. In this study we found that the concentration of oleylamine is critical for the formation of hcp Ni.…”
Section: Refsmentioning
confidence: 95%
“…At a particle size above 10 nm, Co NPs demonstrate FM properties at 20 ° C [32] . Minimum sizes for ferromagnetism at 20 ° C are listed Table 2 .…”
Section: Effect Of Np Sizementioning
confidence: 99%
“…However, cobalt-related high moment nanomaterials are chemically and magnetically unstable in ambient conditions due to their rapid oxidation [2]. Many methods have been developed to synthesize monodispersed superparamagnetic Co nanoparticles (NPs) in the size range below 20 nm with high moment density [3][4][5][6][7][8]. But to produce stable aqueous dispersions of Co NPs for biomedical applications has been very challenging.…”
Section: Introductionmentioning
confidence: 99%